Perbedaan Hasil Belajar Matematika Melalui Metode Team Assisted Individualization dan Metode Drill - Bayu Jaya Tama (SAP (Susunan Artikel Pendidikan), 2017)
This research aims to know whether there is a difference between the mathematics learning results of students taught with a cooperative learning method Team Assisted Individualization and those taught with a drill method. The research is conducted in one of State Senior High Schools in Jakarta. The samples are 60 students randomly taken (simple random sampling) from the population of 80 students from 2 classes. The experimental method is used to distinguish two researched groups, namely an experimental group taught with a cooperative learning method Team Assisted Individualization and a control group taught with a drill method. The research instrument is in the form of 40 multiple-choice questions. The instrument is tested to obtain valid and reliable questions to be used for the research instrument. The validity test on the results of students' mathematics learning with point biserial Correlation formula shows as many as 24 questions are valid and reliable. Before being analyzed, the data are first tested using a pre-requisite test, namely a normality test using lilliefors test and homogeneity test using fisher test. The result of the research shows a difference between the mathematics learning results of students taught with a cooperative learning method Team Assisted Individualization and those taught with a drill method in the State Senior High School in Jakarta.